THE CONCEPT OF ʿAQL AND BRAIN IN THE QURAN AND NEUROSCIENCE: A CONCEPT ANALYSIS OF NĀṢIYAH IN SALMAN’S TAFSIR - Suyadi Suyadi; Mohammad Jailani (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2021)
The purpose of this study is to analyze the meaning of Nāṣiyah in Tafsir Salman from a neo-scientific perspective. The development of neuroscience and Islamic education in this modern era is in line with the emergence of new findings, namely research about the meaning (Nāṣiyah) in the Quran which some commentators define as “the crown” or, in a neuroscience perspective ‘behind the crown’, namely the prefrontal cortex. Data of this research are sourced from literature studies through manual and digital searches, focusing on the Nāṣiyah interpretation paradigm in Surah al-ʿAlaq verses 15-16. Results of the study show that the meaning of Nāṣiyah is identical to the meaning (forehead). In Salman’s interpretation, what is meant by the crown is the brain, especially the prefrontal cortex. Therefore, Nāṣiyah is a neurobiological trace of the brain in the Quran. The discovery of the concept of Nāṣiyah as the neurobiological basis of the brain in the Quran will have broad implications for the development of the potential of ʿaql (reason) in Islamic education. The essence of Islamic education, of which is the development of the potential of reason as a manifestation of brain function (Nāṣiyah) in the Quran.